2006
DOI: 10.1111/j.1745-4514.2006.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Lowering Efficacy of Piperine From Piper Nigrum L. In High-Fat Diet and Antithyroid Drug-Induced Hypercholesterolemic Rats

Abstract: Male Wistar rats were divided into two groups: control diet group and high‐fat diet group (HFD). Both groups were divided into four subgroups, each consisted of 10 animals, and the diets were supplemented with the following ingredients for 10 weeks: (1) 1% carboxymethyl cellulose; (2) 10 mg carbimazole (CM)/kg body weight; (3) 10 mg CM + 40 mg piperine/kg body weight; and (4) 10 mg CM + 2 mg atorvastatin/kg body weight. Feeding HFD to rats significantly (P < 0.05) elevated plasma total cholesterol, triglycerid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…In the present study, rats fed high-cholesterol diet showed a significant increase in serum and hepatic cholesterol, triglycerides (TG), and serum LDL, and decrease in HDL. These findings are consistent with earlier reports [4,35,51]. In the present investigation, supplementation with BT and GT resulted in marked decrease in serum and hepatic cholesterol, TG, and serum LDL, and increased HDL level, when compared with the hypercholesterolemic group.…”
Section: Food Intake (%)supporting
confidence: 96%
“…In the present study, rats fed high-cholesterol diet showed a significant increase in serum and hepatic cholesterol, triglycerides (TG), and serum LDL, and decrease in HDL. These findings are consistent with earlier reports [4,35,51]. In the present investigation, supplementation with BT and GT resulted in marked decrease in serum and hepatic cholesterol, TG, and serum LDL, and increased HDL level, when compared with the hypercholesterolemic group.…”
Section: Food Intake (%)supporting
confidence: 96%
“…It is responsible for many pharmacological activities of the black pepper [24,25]. Piperine is medicinally used as antiinflammatory [26], anti-malarial, cure for stomach ache, weight loss [20,27], anti-leukemia and fever reducer [28]. Pharmacological studies on piperine have revealed that this compound elicited diverse pharmacological activities [29].…”
Section: Introductionmentioning
confidence: 99%
“…Given the broad use of black pepper as spice all over the world, piperine, its most distinct constituent has also already gained significant research attention in the context of cardiovascular disease and a number of in vivo studies suggest that it has antiatherosclerotic activity . While macrophage ChE enhancement is one possible way for a small molecule to exert an antiatherosclerotic effect, the ChE‐inducing potential of piperine has not been studied so far.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research also shows that piperine exhibits beneficial cardiovascular effects in vivo. In rats fed on a high-fat diet enriched with cholesterol and other lipids, elevated plasma levels of HDL and apo A1, and decreased plasma levels of total cholesterol, triglyceride, and LDL cholesterol (LDL cholesterol) were observed in animals supplied with piperine-supplemented food [20][21][22][23]. Another study found that rats fed with high carbo-hydrate, high-fat diet supplemented with piperine displayed normalized blood pressure and improved aortic reactivity [24].…”
Section: Introductionmentioning
confidence: 99%